New media and the challenges of Boko Haram terrorism: proposing the adoption of human-wearable digital technology - Mohammed Ibrahim, Adamkolo; Gujbawu, Mohammed; Abba-Aji, Nassir (Penerbit Universiti Kebangsaan Malaysia, 2019)
The Boko Haram terrorism, which began in 2009 has had a devastating impact on the society. So far, it has triggered one of the worst humanitarian crises in history and has been responsible for over 30 thousand deaths with over two million others displaced, mostly in the North-east of the country with sizeable spillovers into the neighboring countries of Chad, Niger and Cameroon. Boko Haram’s primary goal was to create an Islamic caliphate in the region, and like other terrorist networks, uses the unconventional, hit-and-run guerrilla war tactics. This has rendered the insurgency to be a hard nut to crack, a phenomenon that is cited as one of the main reasons the group is able to continually carry out successful attacks despite being declared “technically defeated”. Hence, this need to seek for alternative, ‘unconventional’ media as a tool for counterterrorism. The media, both new and traditional have been shown to play a critical role toward the de-Bokoharamization campaign of the Nigerian Federal Government in collaboration with its Western partners. However, due to the guerrilla tactics nature of the insurgency, human-wearable digital microchip technology such as radio frequency identification and wireless body area network systems have been suggested as capable of yielding desirable outcomes. Following a critical review of literature and taking from Laswell’s communication model, this review article offers a digital communication counterterrorism model to complement the state’s efforts toward the anti-terrorism campaign.